2011
DOI: 10.1177/1470357211398442
|View full text |Cite
|
Sign up to set email alerts
|

What’s wrong with this picture? an experiment in quantifying accuracy in 2D portrait drawing

Abstract: Traditional portraiture aims to produce a life-like representation of an individual’s unique facial features, but there are a number of perceptual factors that may affect how an artist sees and depicts a sitter’s facial shapes. The anatomical accuracy of a portrait is predominantly ascertained subjectively, and not through quantitative methods. To see if it was possible to apply the methods of analysis more typically used to study variation in biological forms, the authors produced 30 portrait drawings based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 35 publications
0
34
1
Order By: Relevance
“…(Hayes & Milne, 2011, p. 151) Hayes and Milne (2011) found that visual assessment did not coincide with anthropométrie morphometric evaluations of pitch and cant of the head. This suggests that subjective perceptions of the actual visual features of the portraits were inaccurate.…”
Section: Cain's Study and Early Methods Of Drawing Accuracymentioning
confidence: 95%
“…(Hayes & Milne, 2011, p. 151) Hayes and Milne (2011) found that visual assessment did not coincide with anthropométrie morphometric evaluations of pitch and cant of the head. This suggests that subjective perceptions of the actual visual features of the portraits were inaccurate.…”
Section: Cain's Study and Early Methods Of Drawing Accuracymentioning
confidence: 95%
“…All images were then visually assessed for head pose, face shape and facial expression. Head pose was estimated by the position of the ears, which can appear raised in a downwards head pitch and obscured in a head turn [26,28], face shape according to whether it appeared short/wide, tall/thin or an indeterminate combination, and facial expression by the shape of the lips and cheeks, which appear raised during smiling [48,49] [50]), indicating that the right turned faces tend towards a downward pose and vice versa. Visual assessment of faces by one individual is, however, known to be inaccurate with regards to estimating head pose, and requires a minimum of 10 assessors to statistically correlate with the accuracy of a geometric morphometric analysis [26,28].…”
Section: Methodsmentioning
confidence: 99%
“…While neither seems to display an upwards head orientation, both appear to have been taken from an angle above head height, which, on the basis of past forensic photographic comparisons using geometric morphometrics [e.g. 32,[33][34][35], results in a facial morphology that shares some of the shape changes resulting from a downwardly pitched head pose (the upper face is expanded and lengthened while the lower face is contracted and foreshortened [26]). One photograph is of comparatively low resolution and depicts Ms Pearce-Stevenson fairly frontally orientated with a relatively neutral/serious facial expression (Figure 1d), while in the higher resolution photograph her head is turned to the right shoulder (both eyes are visible but the right ear is obscured) and Ms Pearce-Stevenson is displaying a closed-mouth smile (Figure 1e).…”
Section: Materials (I) Photographs Of Ms Pearce-stevenson and The Facmentioning
confidence: 99%
See 2 more Smart Citations